Assessment of colonoscopy screening by elderly people - Sikorski, Piotr; Szamocka, Małgorzata; Meder, Agnieszka; Ameryk, Monika Anna; Świątkowski, Maciej (Journal of Education, Health and Sport, 2017)
Forecasts indicate that in the next decade cancer will become the most common cause of death in our country. Over 140,000 new cases of malignant neoplasms are reported annually in Poland. Colorectal cancer (CRC) is one of the most frequently detected malignancies: third in men and second in women. The aim of the study was the assessment of colonoscopy screening for early detection of colorectal cancer by elderly screening subjects. The study group consisted of 106 elderly people (aged 66 years and older), and the control group consisted of 100 consecutive people aged 40 to 65 years who reported to the Clinic for colonoscopy screening under PBP. Subjects from the control group expressed much more positive opinion about the usefulness of colonoscopy screening. 99,1% of subjects from this group assessed the examination as “very useful”, while in the study group such an opinion was expressed by 76% of subjects (p<0.0001). In the study group, 25.0% of subjects considered the preparation for colonoscopy as not bothersome, while in the control group such an opinion was expressed by 44.3% of subjects (p=0.0040). Due to the poor assessment of colonoscopy screening made by elderly people, a comprehensive analysis of the investigated procedure should be conducted, which should lead to improvements at all of its stages.